Managing Large Donor Influence - Carniol, Michael P.; Fischer, Paul E. (The Accounting Review, 2023)
ABSTRACT Private organizations that produce public goods often receive offers for funding from large donors who seek to influence the nature of the public goods produced. We consider a model in which the potential for large donor influence creates a commitment problem for the organization in the sense that, from an ex ante perspective, the organization sets the price for influence too low given the opportunity cost. Our analysis identifies determinants of the likelihood of large donor influence and assesses various mechanisms that can alleviate or exploit the commitment problem—greater transparency, organization leadership preferences and/or incentives, and targeted small donor campaigns. Finally, we assess how an option to walk back influential large donor contributions or an inability to commit to longer-term agreements with influential donors alters the implications of potential large donor influence. JEL Classifications: D64; L31.